Relationships between dietary acid load, genetic factors and cardiometabolic syndrome on risk of osteoporosis among postmenopausal Chinese women - Lim, Sook Yee (2020)
Evidence is growing that high dietary acid load (DAL), and presence of cardiometabolic syndrome (CMS) might accelerate the rate of bone loss while gene polymorphisms are related to bone deterioration. However, data on DAL among Asian population was scarce with the exception of Hong Kong Chinese. At the same time, empirical evidence showed no clear consensus on the influence of DAL on bone health. The plausible mechanisms of high DAL on bone loss have remained understudied. The unexplored consideration between the links of DAL with CMS traits and single nucleotide polymorphism (SNP) on bone health may explain the contradictory findings. Thus, this study aimed to investigate the relationships between dietary acid load, genetic factors and cardiometabolic syndrome on risk of osteoporosis among postmenopausal Chinese women. At the same time, the study also sought to estimate DAL, vitamin D status, CMS traits and bone resorption rate among postmenopausal women, and to examine the relationships between sociodemographic background, lifestyle factors, anthropometry parameters and biochemical indices with risk of osteoporosis. Taking all together, DAL, CMS and genetic model on risk of osteoporosis among postmenopausal women was developed. This was a cross-sectional study with a total of 211 eligible postmenopausal women were recruited from seven affiliates of the National Council of Senior Citizens Organizations Malaysia. Dietary intake of respondents was assessed using validated interviewer-administered semi-quantitative food frequency questionnaire (FFQ) while DAL was estimated using potential renal acid load (PRAL) and net endogenous acid production (NEAP). Blood was drawn for biochemical parameters and Agena® MassARRAY genotyping analysis was used to identify the IGF1 and IL6 genotypes. Serum collagen type 1 cross-linked C-telopeptide (CTX1) was used as the surrogate bone marker for rate of bone resorption. Interaction between DAL and genetic polymorphisms as well as DAL and CMS were assessed using linear regressions and structural equation modelling. Mean age of respondents was 66.7 ± 6.6 years and mean duration of menopause was 16.1 ± 7.8 years. Approximately 45% of the respondents had low-income and mean years of education was 8.0 ± 4.6. The means of weight and height were 57.9 ± 9.5 kg and 154.0 ± 4.02 cm, respectively. More than one-third of the respondents failed to achieve the recommended duration of physical activity while closed to half of them were poor sleepers. Approximately 70% of the respondents were either serum 25- hydroxyvitamin D deficient or inadequate. Mean PRAL score was 13.8 ± 19.1 mEq/day while mean NEAP score was 72.6 ± 29.3 mEq/day, and were relatively higher than other studies. The mean of CTX1 was 0.45 ± 0.2 μg/L. There were 55.9%, 47.9% and 67.3% of the respondents carried IL6 -572 CC genotype, IGF1 rs35767 CC genotype and IGF1 rs7136446 TT genotype, respectively. In IL6 -174 G/C, all respondents carried the GG genotype, with no C allele was found among the respondents. Binary correlation analysis indicated that age (r = -0.18 p<0.05) and height (r = 0.14, p<0.05) were weakly but significantly correlated with bone resorption. Multiple linear regression showed that younger women, poorer sleeper, higher acidity diet consumption and being IL6 -572 CC genotype carrier were at higher risk of bone resorption. Structural equation modelling demonstrated similar findings with regression analysis, with the addition of the presence of CMS and low vitamin D serum level were the risk factors for higher bone resorption. Besides, there was an unexpected negative association between CMS traits and bone resorption. On the other hand, years of menopausal, years of education, number of diseases, physical activity, weight, BMI, waist circumference, IGF1, DAL-SNPs and DAL-CMS interaction effects were not associated with bone resorption. In conclusion, it is generally acknowledged pathophysiology of osteoporosis and rate of bone loss is a complex process, with multiple factors are involved. Taken together, the current study provides new insight for scientific research on the risk factors for osteoporosis among postmenopausal Chinese women. It is of paramount important to delineate the possible correlations between dietary acid load, CMS traits and genetic factors with bone resorption in other studies. Future studies should also explore how other SNP candidates such as vitamin D receptor (VDR), estrogen receptor beta (ERβ) and transforming growth factor-β1 (TGF-β1) may correlate with risk of bone resorption among postmenopausal women.